Studying the silent side of birdsong - Cardoso, Gonçalo C (BMC Biol, 2014)
The quality of complex communication signals, such as birdsong, is difficult to assess and compare across individuals or species. A new study on skylark song avoids the problem of signal complexity by assessing motor performance during the silent gaps of songs. This provides a metric of song quality applicable to species with very diverse songs, which facilitates novel types of analyses and comparisons in avian bioacoustics. See research article: http://www.biomedcentral.com/1741-7007/12/58.